(untitled) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2024)
This paper firstly aims to catalog the documentation issued by the Aragonese Chancery of Naples, preserved in the main archival institutions in Bari. Secondly, it seeks to analyze the documentation practices employed by this office. The study examines the chancery notes of the thirty-four documents dated between 1454 and 1500, as well as the names and titles of the officials who validated these documents with their signatures. The preliminary results not only corroborate existing knowledge about this chancery but also provide new insights into the processes of document genesis.